LEGAL REGULATION OF RELATIONS UNDER THE AGREEMENT ON THE PROVISION OF CONSUMER LOAN DURING THE MARTIAL LAW IN UKRAINE - Trotsyuk, Nina; Melnychuk, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the purpose of the research paper is to study the concept of «consumer loan» and to disclose the legal regulation of relations under the agreement on the provision of consumer loan in connection with the adoption of the Law of Ukraine No. 2120-IX «On Amendments to the Tax Code of Ukraine and other legislative acts of Ukraine regarding the effect of norms during the martial law». To the defined goal, general and special scientific methods were used, in particular such as: analytical, comparative-legal, system-structural methods, as well as the method of analysis of current domestic legislation. Discussion: search for modern theoretical and methodological approaches to the study of the definition of «consumer loan», the definition of the parties and conditions of the agreement on the provision of consumer loan, the analysis of legislative novels in the sphere of consumer loan in Ukraine during the period of the legal regime of martial law, which provide guarantees to consumers of «microcredit» and provide mechanisms for their protection from unlawful actions, above all, non-bank financial institutions - microfinancial organizations.